RESPONSIBILITY FOR PREMEDITATED MERCENARY MURDER OR CONTRACT KILLING - Mamestsarashvili, Ioseb (European Scientific Journal, ESJ, 2014)
Mercenary is very old, at the same time dangerous stimulus of anti-social action. It originated and evolved along origin and development of the property as negative moral quality of public life.The mercenary motive of a killer is to get some material benefit or release from material expenses. However, murder cannot be considered as a mercenary crime if the aim of an offender is not getting property but maintaining it, even though an offender’s special instinct, greed, etc. is revealed in murder. The variety of mercenary crime is contract killing. Self-interest is clearly expressed in it. Rarely, but it is possible contract killing and mercenary murder not to have any relation. If a killer got the order of murder and committed it with appropriate reward, the action should be qualified under the paragraph “G” of the Part 3 of the Article 109 of the Criminal Code, but order and self-interest should be indicated in the accusation. In this case, the qualification of a crime is not changed, but the double aggravating circumstances may be taken into account in the final sentence. As for an organizer of the murder, if he/she ordered killing without material compensation, depending on the specific situation, his/her action should be qualified as an organizer of contract killing or instigator of the murder.